Bone healing with bortezomib-based regimens in multiple myeloma: a retrospective imaging study. (December 2014) - T'Seyen, Stef; Pans, Steven; Laenen, Anouchka; Devos, Timothy; Dierickx, Daan; Schoemans, Hélène; Delforge, Michel
SUMMARY : Aim : We conducted a retrospective single center study to measure bone healing by conventional x-ray radiographs (CXR) and computer tomography (CT) in multiple myeloma patients treated with bortezomib. Imaging data were correlated with serum levels of alkaline phosphatases and with disease response.Materials & methods : We identified 26 multiple myeloma patients receiving six or more 3-weekly cycles of bortezomib with radiological assessments. Imaging data before, during and after bortezomib, were analyzed for signs of bone healing.Results : In the group of CXR, 8/21 patients (38%) had evidence of bone healing compared with 7/10 patients (70%) in the CT group. Signs of bone healing were observed after an average of 28 (CXR) or 30 (CT) bortezomib administrations. Alkaline phosphatases did not correlate with bone healing or with disease response.Conclusion : In 13/26 (or 50%) of patients a beneficial bortezomib-related skeletal effect could be detected. This retrospective study provides further evidence for skeletal improvement during treatment with bortezomib.